Untangling Eriotheca gracilipes (Malvaceae, Bombacoideae): A new species and a new combination in Eriotheca - Vania Nobuko Yoshikawa; Marília Cristina Duarte (Acta Botânica Brasílica, 2022)
ABSTRACT Eriotheca gracilipes concept is re-circumscribed according to the shape and texture of the leaflets, diameter of the petiole, calyx color, seed striation and geographic distribution. In addition, a new species (Eriotheca uniflora) and a new combination (Eriotheca crenulata) are proposed here. Descriptions, identification key, taxonomic comments, geographic distribution, phenology and conservation status, images of diagnostic characteristics and a table with information about these features are provided for the three species.